DAMPAK IRIGASI TERHADAP KEHIDUPAN SOSIAL EKONOMI PTANI PADI DINAGARI INDERAPURA KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN TAHUN (1082-1999) - Ahmanda, Ronaldo; Sabar, Sabar; Ersi, Livia (Pendidikan Sejarah, 2013)
ABSTRAKÂ This article discusses about the of irrigation forward paddyâs farmers in Nagari Inderapura Â Â Pancung Soal sub- distrct Pesisir Selatan Distric From years 1982-1999 . In The other hand, the formulation of the problem in this started from the field, production, and the effect of paddyâs development whic is development to social ife of society. This social-economic story study research have an objective to see the effect of irigation toloard social-economic life of society at Inderapura Pancung Soal sub-distric. This article use an historical research method which is consist four step such as heuristic ( observation and collecting the data) sources critical as step of selectionÂ  the data, interprestation as a step of analysis the sources which have been found and historiografi is a step of writing. Irigation have olven meanirgfull effectÂ  or advantages to socio-economic life o paddyâs farmer such as : to Increasing societs income at Nagari Inderapura in addition, some good effect which is percelved paddyâs farmer are : first, fulfilled of economic needs of farmer. Second , farmers can keep some money or their in came or they can buy sime valuable stuff such as gold, furniture andÂ  vaelaicle, third, paddyâs farmer can build their house become more better then before, for example. They can renovate a semi-permanent house to be permanent house. Fourth, farmer get move sprit to put their children on high education suchas : ynior high school, senior high schoo and even to Universities. Fifth, Increaing their awareness in health because the have some money on their pocket.Â Â Key words : Peasants, Irigation and Social Chang